2020
DOI: 10.1016/j.ijid.2020.05.124
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for surgical site infection after colorectal surgery: A multiple-center prospective study of 3,663 consecutive patients in China

Abstract: Background: Surgical site infection (SSI) after colorectal surgery (CRS) remains a significant problem for its negative clinical outcomes. However, it is poorly understood in China. This study aims to investigate the incidence, risk factors and microbiology of SSI after CRS. Methods: A nationwide prospective multicenter design was applied. Patients in 19 Chinese hospitals from 2015 to 2018 were prospectively monitored for SSI after CRS. Demographic data, hospital characteristics, and potential perioperative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Surgical site infections (SSIs) are the most frequently reported type of healthcare-associated infection, accounting for approximately 20% of all healthcare-associated infections in the United States [1] and in Europe [2] SSIs lead to reoperation, delayed discharge from hospital, reduced quality of life, and increased mortality rates [3][4][5]. The incidence of SSI in gastrointestinal surgery is significantly higher than that in surgical procedures on other organ sites [6,7], ranging from 3.7-6.4% in colorectal surgery [8][9][10][11] to 3.6-14.2% in gastric surgery [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical site infections (SSIs) are the most frequently reported type of healthcare-associated infection, accounting for approximately 20% of all healthcare-associated infections in the United States [1] and in Europe [2] SSIs lead to reoperation, delayed discharge from hospital, reduced quality of life, and increased mortality rates [3][4][5]. The incidence of SSI in gastrointestinal surgery is significantly higher than that in surgical procedures on other organ sites [6,7], ranging from 3.7-6.4% in colorectal surgery [8][9][10][11] to 3.6-14.2% in gastric surgery [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies may opt to investigate even larger sample sizes and include more variables if possible. Sixth, previous studies have shown that junior surgeons may pose an increased risk (OR = 2.4) of surgical site infections as reported by Hou et al 21 . In our study, there were a number of different surgeons in each subspecialty.…”
Section: Discussionmentioning
confidence: 81%
“…Overall, in this study, we identi ed 56 cases (23.33%) of SSI among 240 cases of colon cancer surgery. In different studies, the results show that the incidence of SSI ranges from 3.6% [19] and 3.3% [20] to 32.1% [20], which may be due to the fact that in some studies the de nition of SSI is different. Also, the period of time that patients are followed is different in each study [21][22][23].…”
Section: Discussionmentioning
confidence: 98%